The plasmid vectors, pBS2ndd and pBS3ndd, for versatile cloning with low background in Escherichia coli - Tiwa Rotchanapreeda (2019)
© 2018, Springer Science+Business Media B.V., part of Springer Nature. Abstract: For decades, diverse plasmid vectors have been continuously developed for molecular cloning of DNA fragment in the bacterial host cell Escherichia coli. Even with deliberate performances in vector preparation, the cloning approaches still face inevitable background colonies, or false positive clones, that may be arisen from intact or self-ligated plasmid molecules. To assist in such problem, two plasmids, pBS2ndd and pBS3ndd, which resistant to ampicillin and kanamycin respectively, were developed in this study as more advantageous cloning vector. The plasmids carry ndd, a lethal gene from bacteriophage T4 coding for nucleoid disruption protein that binds to the host chromosome and progressively kill the cell. The deadly toxicity of Ndd inhibits host cells that obtain intact or ndd-religated vector from growing, which results in low background and dramatically reduces the effort for selection of recombinants. Moreover, their identical multiple cloning site was designed to support various cloning strategies. Digestion of plasmids with XcmI allows for in vitro T/A ligation, while with EcoRV permits blunt-end ligation, with capability of blue-white colony screening. In vivo homologous recombination cloning is also utilizable by amplification of insert fragments using primers containing homology arms and transformation into capable E. coli strains. To demonstrate their advantages, the plasmids were used to clone PCR product samples for DNA sequencing with low-background and versatile cloning strategies. Such rapid and cost-effective cloning procedures are also proposed here. Finally, the cloning for protein expression with blue-white selection was also possible using egfp as a model regulated by lac and T7 promoters on the plasmid or other build-in promoters with the insert.